Diagnostic and prognostic accuracy of miR-21 in renal cell carcinoma: a systematic review protocol. Issue 1 (4th January 2016) - Rasti, Arezoo; Mehrazma, Mitra; Madjd, Zahra; Keshtkar, Abbas Ali; Roudi, Raheleh; Babashah, Sadegh
Abstract : Introduction: Renal cell carcinoma (RCC) is the most common neoplasm in adult kidneys. One of the most important unmet medical needs in RCC is a prognostic biomarker to enable identification of patients at high risk of relapse after nephrectomy. New biomarkers can help improve diagnosis and hence the management of patients with renal cancer. Thus, this systematic review aims to clarify the prognostic and diagnostic accuracy of miR-21 in patients with RCC. Methods and analysis: We will include observational studies evaluating the diagnostic and prognostic roles of miR-21 in patients with renal cancer. The index test and reference standards should ideally be performed on all patients. We will search PubMed, SCOPUS and ISI Web of Science with no restriction of language. The outcome will be survival measures in adult patients with RCC. Study selection and data extraction will be performed by two independent reviewers. QUADAS-1 will be used to assess study quality. Publication bias and data synthesis will be assessed by funnel plots and Begg's and Egger's tests using Stata software V.11.1. Ethics and dissemination: No ethical issues are predicted. These findings will be published in a peer-reviewed journal and presented at national and international conferences. Trail registration number: This systematic review protocol is registered in the PROSPERO International Prospective Register of Systematic Reviews, registration number CRD42015025001.